2005
DOI: 10.1080/14733140600571326
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with improvement after brief psychological interventions in primary care? Issues arising from using routine outcome measurement to inform clinical practice

Abstract: Study purpose: This descriptive study used a routine practice dataset to investigate whether demographic variables and intervention length were associated with outcome after brief psychological interventions in primary care. Brief description of the participants: The data are from 3687 adults with a wide range of presenting problems, from a culturally diverse inner London borough, referred to primary care psychologists and counsellors. Methodology: Demographic and service activity data were routinely collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This study indicates the benefits of using routinely collected large datasets to address research questions of interest to counsellors and psychotherapists (Mellor-Clark et al, 2001;Shepherd et al, 2006). The analysis of routine data in terms of individual characteristics and covariates can increase understanding regarding those clients that are more likely to drop-out of therapy.…”
Section: Methodological Issuesmentioning
confidence: 87%
See 2 more Smart Citations
“…This study indicates the benefits of using routinely collected large datasets to address research questions of interest to counsellors and psychotherapists (Mellor-Clark et al, 2001;Shepherd et al, 2006). The analysis of routine data in terms of individual characteristics and covariates can increase understanding regarding those clients that are more likely to drop-out of therapy.…”
Section: Methodological Issuesmentioning
confidence: 87%
“…The short‐term efficacy of counselling has been well documented (Bower and Rowland, ), and its effectiveness in NHS Primary Care practice has been supported by studies of large routinely collected datasets (Mellor‐Clark, Connell, & Barkham, ; Shepherd, Ashworth, Evans, Robinson, Rendall, & Ward, ). These datasets also indicate a proportion of clients having a level of psychological distress similar to clients treated in secondary care (Barkham, Gilbert, Connell, Marshall, & Twigg, ), even though the application of counselling to more severe conditions such as severe depression has not been supported by National Institute for Health and Clinical Excellence (NICE) guidelines (NICE, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although efforts have been made to improve multicultural awareness in clinicians, the trend of minority under-utilization and premature termination continues to be reported (e.g., Austin and Wagner 2006;Diaz et al 2005;King and Canada 2004;Shepherd et al 2005;Staudt 2003). The current findings would suggest that discussion and evaluation of reporter differences may provide one more avenue of intervention designed to make psychological services more available to minority members.…”
Section: Discussionmentioning
confidence: 95%
“…The Clinical Outcomes in Routine EvaluationOutcome Measure (CORE-OM; Evans et al, 2000) is a 34-item self-report measure, which is widely used in the UK and shown to be reliable, valid and acceptable in a range of settings (Barkham et al, 2002;Evans, Connell, Barkham, Marshall, & Mellor-Clark, 2003;Shepherd et al, 2005). The items cover four domains: subjective well-being, problems/symptoms, life functioning and risk.…”
Section: Introductionmentioning
confidence: 99%